Outcome of pregnancy after in vitro fertilization: A retrospective cohort study - Gordana Grgić; Anis Cerovac; Azra Hadžimehmedović; Selma Muratović; Asja Terzić; Ermin Čehić (Medicinski glasnik, 2026)
Aim: To determine the outcome of pregnancies in women whose pregnancies resulted from in vitro fertilisatio (IVF) procedure. Methods: This a retrospective cohort study was conducted at the Clinic for Gynecology and Obstetrics, University Clinical Center Tuzla, Bosnia and Herzegovina. Data from the delivery protocol were analyzed over a five-year period, from January 1, 2019, to December 31, 2023. A total of 257 deliveries from IVF pregnancies were analyzed, constituting the study group, while the control group consisted of an equal number of women with spontaneously conceived pregnancies. The following data were analyzed: baseline obstetrics and neonatal characteristics, and presence of complications during pregnancy and delivery. Results: The average age of pregnant women was higher in the study compared to the control group (p=0.001). The average body weight and body length at birth were lower in the study group (p=0.001). The twin pregnancies were more frequent in the study group (p=0.0001). In the study group it was recorded largest number of primiparous women (p=0.0001). It was found higher number of newborns with Apgar scores <7 at the first and fifth minutes in the study group (p=0.0001). There were higher prevalence of preterm births and cesarean section in the study group (p=0.0001). Fetal asphyxia and breech presentation were more prevalent in the study group (p=0.008 and p<0.0001). Consclusion Pregnancies resulting from IVF were still riskier than those resulting spontaneously.
Keywords: asphyxia neonatorum; Cesarean section; premature birth; pregnancy; Twin